Pre-mayoral Career and Incumbency of Local Leaders in Post-Communist Countries: Evidence from Lithuania and Slovenia - Kukovic, Simona; Lazauskienė, Aistė (Political Preferences, 2018)
Political careers emerge when individuals develop patterns of mobility between offices in the political realm. These patterns provide useful clues about the expected activity of an individual leader. Patterns of political tenure can be revealing because individuals who aspire to long-term service seem more committed to the autonomy of their institutions, as well as more active and effective within them. The mayoral career is created in a continuous process of mayoral position implementation where a unique combination of ambition and opportunity intertwine. A political career is therefore necessarily associated with time and defined by two key points: the starting point and the termination point of mayoral function. Between them, the mayoral career takes place. The article focuses on the career development and mayoral incumbency in post-communist countries such as Lithuania and Slovenia. Authors particularly focus on the direct mayoral elections conducted in Lithuania for the first time in 2015 and introduced in Slovenia already in 1994. Career of local leaders was analysed in terms of pre-mayoral career, where authors discovered that the largest share of mayors were municipal council members. Both countries had a relatively high proportion of political newcomers. In Lithuania, the first direct elections finally also enabled the elections of non-partisan candidates, a trend seen in Slovenia since 1994. Key words: pre-mayoral political career, incumbency, direct elections, non-partisans, Post-communist countries